The need and scope for strengthening co-operation between regional financing arrangements and the IMF - Ulrich Volz (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
This article makes the case for strengthening co-operation between regional financing arrangements (RFAs) and the International Monetary Fund (IMF), and examines ways to do so. It argues that ex ante co-operation between RFAs and the IMF is needed to reduce the risk of co-operation failing in the middle of a crisis, to help avoid “forum shopping” and institutional arbitrage, to prevent weakening the IMF's role as the guardian of global financial stability, to minimise duplication, and to generate mutual benefits from a division of labour and specialisation based on the comparative advantages of the respective institutions. It calls for guidelines for organising the inter-institutional relations between the IMF and RFAs, a clear division of labour in crisis lending, and co-operation and exchange in surveillance and analysis. Co-operation with RFAs should be seen as a chance for the IMF to overcome its stigmatisation, strengthen its global role and ensure its continued relevance.
Keywords: 330; Internationales Finanzsystem; Regionale + globale + transnationale Governance